Development of transgressive Tongil varieties to increase yield potentials in irrigated and rainfed lowlands - CGIAR Research Program on Rice (2019)
In early yield testing, amongst 68 promising Tongil lines, 16 lines yielded between 9.1-14.6 ton/ha (9-71% higher than the best checks. These transgressive Tongil (indica/japonica intraspecifics) lines are now being tested in further yield trials in irrigated lowlands in Senegal and in rainfed lowlands of Senegal, Ghana and Mali.